Restructuring rural settlements based on an analysis of inter-village social connections: A case in Hubei Province, Central China. (October 2016) - Tian, Yasi; Kong, Xuesong; Liu, Yaolin; Wang, Haofeng
Abstract: Social connections are the consequences and causes of rural settlement distribution. Although numerous studies have examined rural restructuring, the relationship between social connections and rural restructuring has been neglected. This study proposed a novel restructuring method of rural settlement based on an analysis of inter-village social connections that include both spatial and non-spatial connections. A questionnaire survey was conducted from a sample comprising 925 people from Chengui Township in Hubei Province, Central China. The characteristics of the social networks of the residents were analyzed using a node degree and node symmetry index ( NSI ), and the causes of network formations were analyzed according to the connection types of the rural residents. Both consolidated settlements and relocation areas were identified using a measurement of ideal radius based on social connection analysis. Spatial connection orientation, non-spatial orientation and ideal radius orientation were proposed to guide rural settlement restructuring. The results indicated that the hierarchy of village-town systems can be effectively identified by the features of social connection networks. Social connection strength is an important guiding factor for rural reconstruction. This study puts forward a new view of rural settlement reconstruction and aids in our understanding of both the changing mechanism of rural settlement and the relationship between social connections and rural settlement reconstruction. Highlights: This paper advances our understanding of the relationship between social connections and rural settlement reconstruction. The features of inter-village social connection network were analyzed spatially and non-spatially. Social connection analysis contributes to the identification and planning of village-town systems. Three restructuring directions were distinguished based on the analysis of social connection strength and ideal radius.